Cisplatin-induced ototoxicity in pediatric solid tumors: The role of glutathione S-transferases and megalin genetic polymorphisms - Worawut Choeyprasert (2018)
Cisplatin-induced ototoxicity, an important dose-limiting side effect, has proven high interindividual variability. Glutathione S-transferases (GSTs) are isoenzymes involved in cellular detoxification processes. Megalin has been demonstrated to bind aminoglycosides, known to be similar to cisplatin for their ototoxicity. The GSTs and megalin expression is genetically polymorphic, which might be responsible for the variability in cisplatin-induced ototoxicity. The genotyping of GSTM1, GSTT1 polymorphisms, and 2 nonsynonymous single nucleotide polymorphisms (SNPs) at megalin genes, rs2075252 and rs2228171, were performed in 68 children diagnosed with solid tumors who received cisplatin-based chemotherapy. After the end of treatment, audiometry demonstrated hearing loss in 79.4% of patients according to Brock classification. The cumulative cisplatin dose > 400 mg/m 2 is associated with increased risk of cisplatin-induced ototoxicity [odds ratio (OR), 17.5; 95% confidence interval (CI), 3.09-98.62]. GSTT1 wild genotype and C-allele of rs2228171 SNPs of megalin gene occurred with higher frequency in patients with ototoxicity (P =0.023; OR, 10; 95% CI, 1.80-56.00 and P=0.034; OR, 2.67; 95% CI, 1.22- 5.82, respectively). In conclusion, our results suggested that GSTT1 wild genotype and C-allele of rs2228171 SNPs might be risk factors for ototoxicity. The cumulative cisplatin dose < 400 mg/m 2 should be beneficial in order to ameliorate ototoxicity. Copyright © 2012 by Lippincott Williams & Wilkins.